The full cost would be £33.75
Answer:
The third choice: (x² - 1)³
Step-by-step explanation:
That is the only expression that is a binomial. Binomial means "two numbers". For this expression, x² is one number, and -1 is the other. Choice 1 is a monomial (one number) and choices 2 and 4 are trinomials (three numbers)
Answer:
-6<w<8
Step-by-step explanation:
-6<w<8
Answer:
$88.00
Step-by-step explanation:
66=3/4x
66/.75=66*4/3=88
I'll do the first one to get you started
So we have g(f(x)) which means that we start with g(x) and replace the 'x' with 'f(x)' to get g(f(x))
g(x) = ( x - 4 )/2
g(f(x)) = ( f(x) - 4)/2 .... replace every x with f(x)
g(f(x)) = (2x+4-4)/2 .... replace f(x) on the right side with 2x+4
g(f(x)) = (2x+0)/2
g(f(x)) = (2x)/2
g(f(x)) = 1x/1
g(f(x)) = 1x
g(f(x)) = x
Let me know if you need help with the other one.